2015
DOI: 10.13075/ijomeh.1896.00359
|View full text |Cite
|
Sign up to set email alerts
|

Association between sleep duration and sleep quality, and metabolic syndrome in Taiwanese police officers

Abstract: Objectives: This study's objective was to examine association between sleep duration and sleep quality, and metabolic syndrome (MetS) and its components in Taiwanese male police officers. Material and Methods: Male police officers who underwent annual health examinations were invited to join the study and eventually a total of 796 subjects was included in it. The study subjects were divided into 5 groups according to the length (duration) of sleep: < 5, 5-5.9, 6-6.9, 7-7.9 and ≥ 8 h per day, and the global Pit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 36 publications
3
38
0
5
Order By: Relevance
“…Taiwanese male police officers [30]. Similarly, another study reported that to some extent, females with elevated sleep disturbance scores had greater odds of abdominal obesity than those without [6].…”
Section: Characteristics Of Participantsmentioning
confidence: 90%
“…Taiwanese male police officers [30]. Similarly, another study reported that to some extent, females with elevated sleep disturbance scores had greater odds of abdominal obesity than those without [6].…”
Section: Characteristics Of Participantsmentioning
confidence: 90%
“…Also, an association was observed between the presence of sleep disorders and clinical outcomes such as depression, burnout, diabetes and cardiovascular disease. (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)26) In the other study, the clinical and polysomnography data of 761 military officers were evaluated retrospectively, showing a high prevalence of OSAS (27.2%), insomnia (24.7%) and insufficient sleep time (41.8%). (14,27) The main predictors of OSAS were obesity, male gender and age.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disorders were associated with metabolic syndrome and abdominal obesity. Police officers who slept less than 5 h were more likely to suffer from abdominal obesity than those who slept 7-7.9 h. (16) OSAS, the sleep disorder most frequently diagnosed in police officers, has been involved as an independent risk factor for cardiovascular disease, diabetes, cardiac arrhythmias, plurimetabolic syndrome, traffic accidents and death. (17,18,25) OSAS has also been associated with significant cognitive decline and difficulty to maintain vigilance and attention during work.…”
Section: Discussionmentioning
confidence: 99%
“…According to metabolic syndrome (MetS) criteria, abnormalities of health check-up results were marked if the subjects had any of the following risk determinants [14]: -central obesity -waist circumference ≥ 90 cm in men and ≥ 80 cm in women; -elevated blood pressure -systolic blood pressure (SBP) ≥ 130 mm Hg or diastolic blood pressure (DBP) ≥ 85 mm Hg; -hyperglycemia -fasting sugar ≥ 100 mg/dl; -hypertriglyceridemia -triglycerides ≥ 150 mg/dl; -hypo-HDL cholesterolemia -HDL < 40 mg/dl in men and < 50 mg/dl in women. Although NSW were the youngest among all 3 subgroups, they had significantly higher rates for metabolic abnormalities than the daytime workers (CDW and DSW) did.…”
Section: Covariatesmentioning
confidence: 99%